Management of Digital Literacy-Based Work Practice Training in The Boarding School Environment - Muhammad Nawawi Fathullah; Ulfiah Ulfiah; Agus Mulyanto; Muhammad Andriana Gaffar; Ahmad Khori (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
The purpose of the study which became the focal point was the management of work practice training based on digital literacy in the boarding school environment. This study uses a qualitative approach with a case study method of data collection is done by triangulation techniques using interviews, document studies, and field observations. With the object of research at the community work Training Center (BLKK) vocational Information Technology and Al-Mizan Islamic boarding school, Jatiwangi District, Majalengka Regency, West Java province. The results showed that: 1) the planning of training programs in BLKK Al-Mizan that focuses on identifying training needs has been carried out in accordance with SOP or rules, regulations of the Ministry of manpower. 2) the development of training programs in BLKK Al-Mizan which focuses on internal training cooperation still occurs in the dichotomy of departments and sectoral egos and external cooperation with less developed companies and even tiered apprenticeship program cooperation no longer exists. 3) the implementation of the training Program at BLKK Al-Mizan focusing on the implementation of competency-based training (CBT) has not been fully implemented. 4) evaluation of training at BLKK Al-Mizan showed that the assessment of training services has been carried out but the results are limited to the basis for recognition of students and the Al-Mizan Islamic boarding school environment. 5) support the function and use of training management at BLKK Al-Mizan to the function of improving digital literacy in the Al-Mizan Islamic boarding school. The researcher concluded that the management of digital literacy-based work practice training in the boarding school environment runs effectively and equips students to be technologically literate, this is also reflected in the students themselves in the use of digital-based books.